Factors Affecting Adolescent Coping with Narcissistic Personality: Literature Review - Cecilia Indri Kurniasari (Indonesian Journal of Global Health Research, 2023)
Narcissistic personality is a personality disorder that is often experienced by groups of teenagers in this modern technological era. This era causes various significant changes in aspects of life. Adolescents must have positive coping to adapt to significant changes in the environment, human resources and technological resources. Adolescents who cope negatively with these changes are at risk of developing narcissistic disorders. Adolescents with untreated narcissistic disorder may develop a narcissistic personality as a result of the condition's effects on their personality. The purpose of this review was to identify the factors affecting adolescents coping with narcissistic personalities. This review employed a literature review, with references sourced from articles/journals published between 2012 and 2022. Electronic databases such as PubMed, CINAHL, Wiley Online Library, and SpringerLink were used to conduct article searches. Several related research publications were obtained throughout the article search, including 1 from the Wiley Online Library, 47 from PubMed, 1 from CINAHL, and 419 from SpringerLink. From all of those articles, only five articles can be continued to analyze. All of five articles were review with inclusion and exclusion criteria to find factors influencing adolescents coping with a narcissistic personality. The findings of the synthesis of various articles show that both internal and external coping sources have an impact on adolescents' individual coping with a narcissistic personality. Internal factors consist of physical health, belief systems including beliefs or religion, commitments or life principles, feelings or emotional self, and social skills. Meanwhile, external factors include social support and material resources (economic conditions, home environmental conditions, and social relationship conditions).